Changes in submerged aquatic vegetation (SAV) coverage caused by extended drought and flood pulses. (3rd April 2018) - Shivers, Stephen D.; Golladay, Stephen W.; Waters, Matthew N.; Wilde, Susan B.; Ashford, Philip D.; Covich, Alan P.
ABSTRACT: Shivers SD, Golladay SW, Waters MN, Wilde SB, Ashford PD, Covich AP. 2018. Changes in submerged aquatic vegetation (SAV) coverage caused by extended drought and flood pulses. Lake Reserv Manage. 34:199—210. Previous studies demonstrated that submerged aquatic vegetation (SAV) affects productivity and biogeochemical cycling within freshwater ecosystems. Some invasive submerged macrophytes dominate shallow water bodies and are known to compete for nutrients with native macrophytes and phytoplankton. To evaluate variation in SAV coverage, annual whole-reservoir vegetation surveys were conducted during the peak of the growing season over a 3-yr period that included drought and years with seasonal flood pulses. Physical parameters were directly measured (Photosynthetically Active Radiation: PAR) or obtained from USGS river gauges (river discharge and turbidity) to investigate the relationship between hydrology and SAV coverage. Precipitation was lower in the first year of the study compared to the following 2 yr causing the lowest river discharge observed over the 3-yr study. First-year discharge was also lower than the 50-yr median daily Q (discharge). SAV coverage, particularly of dioecious Hydrilla verticillata, was the greatest during the reduced flow period (35.5 km 2 ). With increasing precipitation and river discharge, SAV coverage was reduced during subsequent years (22.9 km 2 and 18.3 km 2, respectively). Increased discharge caused turbidity to increase, which reduced light availability during the early growing season, causing a delay in germination and subsequent reduction in SAV coverage. In shallow reservoirs, SAV is capable of extensive coverage. Thus, large variation in coverage can alter ecosystem functionality. In regulated river systems, managing late spring flood pulses may provide some control of SAV coverage in shallow reservoirs, in addition to providing other environmental flow benefits.